A multi-resolution SPH method for fluid-structure interactions - Zhang, Chi; Rezavand, Massoud; Hu, Xiangyu (Journal of computational physics, 2021)
•Different spatial-temporal resolution for fluid and solid structure.•Position-based Verlet time integration scheme.•Time-averaged velocity and acceleration to enhance structure-fluid force matching. In this paper, we present a multi-resolution smoothed particle hydrodynamics (SPH) method for modeling fluid-structure interaction (FSI) problems. By introducing different smoothing lengths and time steps, the spatial-temporal discretization is applied with different resolutions for fluid and structure. To ensure momentum conservation at the fluid-structure coupling, a position-based Verlet time integration scheme is introduced. Furthermore, the time-averaged velocity and acceleration of solid particles are introduced to enhance force matching in the fluid and solid equations. A set of numerical examples including several bio-mechanical problems are considered to demonstrate the efficiency, accuracy and robustness of the present method. An open-source code for all the examples is also provided.